Characterization of Two Glycoside Hydrolases of Family GH13 and GH57, Present in a Polysaccharide Utilization Locus (PUL) of Pontibacter sp. SGAir0037 - Hilda Hubertha Maria Bax; Edita Jurak (Molecules, 2024)
Glycogen, an α-glucan polymer serving as an energy storage compound in microorganisms, is synthesized through distinct pathways (GlgC-GlgA or GlgE pathway). Both pathways involve multiple enzymes, with a shared glycogen branching enzyme (GBE). GBEs play a pivotal role in establishing α-1,6-linkages within the glycogen structure. GBEs are also used for starch modification. Understanding how these enzymes work is interesting for both glycogen synthesis in microorganisms, as well as novel applications for starch modification. This study focuses on a putative enzyme GH13_9 GBE (PoGBE13), present in a polysaccharide utilization locus (PUL) of Pontibacter sp. SGAir0037, and related to the GlgE glycogen synthesis pathway. While the PUL of Pontibacter sp. SGAir0037 contains glycogen-degrading enzymes, the branching enzyme (PoGBE13) was also found due to genetic closeness. Characterization revealed that PoGBE13 functions as a typical branching enzyme, exhibiting a relatively high branching over non-branching (hydrolysis and α-1,4-transferase activity) ratio on linear maltooctadecaose (3.0 ± 0.4). Besides the GH13_9 GBE, a GH57 (PoGH57) enzyme was selected for characterization from the same PUL due to its undefined function. The combined action of both GH13 and GH57 enzymes suggested 4-α-glucanotransferase activity for PoGH57. The characterization of these unique enzymes related to a GlgE glycogen synthesis pathway provides a more profound understanding of their interactions and synergistic roles in glycogen synthesis and are potential enzymes for use in starch modification processes. Due to the structural similarity between glycogen and starch, PoGBE13 can potentially be used for starch modification with different applications, for example, in functional food ingredients.